Milk metabolite profiling of dairy cows as influenced by mastitis - Du, Chao; Zhao, Xuehan; Zhang, Shujun; Chu, Chu; Zhang, Xiaojian; Teng, Zhanwei (Frontiers in Veterinary Science, 2024)
Mastitis is a disease with frequent incidence in dairy cows, causing huge financial losses to the dairy industry globally. The identification of certain biomarkers is crucial for the early diagnosis and management of mastitis. Metabolomics technology is a useful tool to accurately and efficiently analyze the changes of metabolites in biofluids in response to internal and external stimulations. Milk is the secreted by udder, and milk metabolites can directly reflect whether the udder are in the healthy or diseased state. The milk metabolomics analysis of mastitis can reveal the physiological and pathological changes of mammary gland and screen the related biomarkers, so as to offer useful reference for the prediction, diagnosis, and management of mastitis. Therefore, the aim of the present study was to comprehensively summarize milk metabolic change caused by naturally occurring or experimentally induced mastitis in dairy cows. In addition, comparative analysis and enrichment analysis were conducted to further discover potential biomarkers of mastitis and to identify the relevant pathways differentiating the healthy and mastitic cows. Multiple milk metabolites were identified to be altered during mastitis based on different metabolomics platforms. It was noteworthy that there were 28 metabolites not only identified by at least two different studies, but also showed consistent change tendency among the different studies. By comparison with literature, we further identified 12 milk metabolites, including acetate, arginine, β-hydroxybutyrate, carnitine, citrate, isoleucine, lactate, leucine, phenylalanine, proline, riboflavin, and valine that were linked with the occurrence of mastitis, which suggested that these 12 milk metabolites could be potential biomarkers of mastitis in dairy cows. Several pathways were revealed to explain the mechanisms of the variation of milk metabolites caused by mastitis, such as phenylalanine, tyrosine and tryptophan biosynthesis, arginine and proline metabolism, riboflavin metabolism, and tricarboxylic acid (TCA) cycle. These results offer a further understanding for the alteration of milk metabolites caused by mastitis, which have a potential significance in the development of more reliable biomarkers for mastitic diagnosis in dairy cows.